Green electroluminescence from an n-ZnO : Er/p-Si heterostructured light-emitting diode - Iwan, S. (2013)
Erbium-doped ZnO (ZnO:Er) thin films with various doping concentrations were deposited on p-Si substrates by ultrasonic spray pyrolysis (USP). The n-ZnO:Er/p-Si heterojunctions were further employed to fabricate light-emitting diodes (LEDs). The devices showed diode-like rectifying current–voltage characteristics with a low reverse breakdown voltage, attributed to the avalanche breakdown. A distinct green electroluminescence peaking at 537 nm and 558 nm were observed at room temperature under reverse bias. The green electroluminescence originated from the electron impact excitation of Er3+ ions doped in ZnO films.